Pengaruh Kecerdasan Emosi Guru, Beban Mengajar Guru dan Kepemimpinan Transformasional Kepala Sekolah terhadap Kinerja Guru di Yayasan Kalam Kudus Indonesia Cabang Bali - M.A. Patty; D. G. H. Divayana; I. P. W. Ariawan (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study aims to find out how the teacher’s emotional intelligence, teacher workload, transformational leadership of the principal affect the performance of teachers at Yayasan Kalam Kudus Indonesia Bali. This form of research using ex-post facto research by taking a sample 51 from a population of 72 teachers at all levels at Yayasan Kalam Kudus Indonesia Bali. Researcher collected the data through questionnaires with the Likert Scale. Test conducted to analyze data by conducting F Test, T Test, Coefficient Test, Correlation Test and Double Regression Test with the help of SPSS version 25 application. The result of the study were 1) Emotional Intelligence has a significant influence on Teacher's Performance, can be seen from the thit value of 6,182 > ttab 1.67793 and Sig 0.00 > 0.05. R count of 0.740 indicates the rate of relationship between variables is high. 2) Teacher Workload has no significant effect on Teacher Performance, judging by the Sig value. 0.188 > 0.005. Coefficient of Workload to Performance of – 0.051 indicates that if workload decreases then Performance will increase (inversely proportional). 3) The Principal's Transformational Leadership connects linearly with Teacher Performance and significantly affects Teacher Performance, judging by the thit of 2,209 > ttab 1.67793 and Sig 0.032 < 0.005. 4) Simultaneously significant positive influence between Teacher Emotional Intelligence, Teacher Workload and Principal Leadership with Teacher Performance by making a Relative Contributions of 100% and Effective Contribution of 60,7%.